Self‐Assessment of Comprehensibility and Accentedness in Second Language Korean. Issue 3 (3rd April 2022) - Isbell, Daniel R.; Lee, Junkyu
Abstract: This study investigated L2 Korean speakers' self‐assessment of speech comprehensibility and accentedness, including a conceptual replication of Trofimovich, Isaacs, Kennedy, Saito, and Crowther (2016, Experiment 1) and exploratory analyses of individual differences in self‐assessment. L2 Korean speakers ( N = 198) self‐assessed their comprehensibility and accentedness using 9‐point scales, rated their satisfaction with their pronunciation and the value (importance) of pronunciation on 9‐point scales, completed a background questionnaire, and recorded a monologic speaking task. L1 Korean listeners ( N = 82) judged 28 randomly assigned speakers for comprehensibility and accentedness using 9‐point scales, and scores for each speaker were adjusted to account for variation in listener severity. Listener and self‐assessments for both comprehensibility and accentedness correlated moderately ( r = .54). Individuals with lower listener‐based scores tended to overestimate their ability in self‐assessment and vice versa, but higher listener‐based scores were associated with smaller absolute miscalibration. Regression analyses suggested that pronunciation satisfaction and perceived value of pronunciation both influenced self‐assessment scores and calibration. Abstract :